Galaxy fields of LISA massive black hole mergers in a simulated universe. Issue 4 (10th January 2023) - Lops, Gaia; Izquierdo-Villalba, David; Colpi, Monica; Bonoli, Silvia; Sesana, Alberto; Mangiagli, Alberto
ABSTRACT: Laser Interferometer Space Antenna (LISA) will extend the search for gravitational waves (GWs) at 0.1 - 100 mHz where loud signals from coalescing binary black holes of 10^4 - 10^7 M_ are expected. Depending on their mass and luminosity distance, the uncertainty in the LISA sky-localization decreases from hundreds of deg 2 during the inspiral phase to fractions of a deg 2 after the merger. By using the semi-analytical model L-Galaxies applied to the Millennium-I merger trees, we generate a simulated universe to identify the hosts of z 3 coalescing binaries with total mass of 3 × 10^5, 3 × 10^6, and 3 × 10^7 M_, and varying mass ratio. We find that, even at the time of merger, the number of galaxies around the LISA sources is too large ( 10^2 ) to allow direct host identification. However, if an X-ray counterpart is associated to the GW sources at z < 1, all LISA fields at merger are populated by 10 active galactic nuclei (AGNs) emitting above 10^-17 erg cm^-2 s^-1 . For sources at higher redshifts, the poorer sky-localization causes this number to increase up to 10^3 . Archival data from eRosita will allow discarding 10 per cent of these AGNs, being too shallow to detect the dim X-ray luminosity of the GW sources. Inspiralling binaries in an active phase with masses 10^6 M_ at z 0.3 can be detected, as early as 10 h before the merger, by future X-ray observatories in less than a few minutes. For these systems, 10 AGNs are within the LISA sky-localization area. Finally, the LISA-Taiji network would guarantee the identification of an X-ray counterpart 10 h before merger for all binaries at z 1 .